Nurses’ Existential Spirituality, Nursing Oncological Patients - Petravičienė, Zita; Bartašiūnienė, Vida; Paplauskas, Henrikas (Slauga. Mokslas ir praktika, 2022)
The phenomenon of nurses’ spirituality is relevant in the holistic nursing of oncological patients, providing spiritual care. Its basis is the phenomenon of spirituality, i. e. the aspect of spirituality is felt, experienced. The nurse, providing spiritual care, shall know and reflect the phenomenon of spirituality herself/himself, in her/his own life. The aim of the research is to reveal the existential spirituality of nurses, taking care of oncological patients. The research issue (problem) includes the following main questions: How do nurses, taking care of oncological patients, reflect spirituality in their own practical activities? How do nurses reflect on the nurse‘s and the patient‘s spiritual relationship, providing care for oncological patients? A qualitative research was conducted at National Cancer Institute, Unit X, using an interview method. The existential spirituality of nurses is revealed, performing their favourite work, in which they do realize themselves and have the opportunity to improve themselves, to communicate with patients, and create an empathetic relationship with them. The internal strength for nurses is provided by knowledge, experience at work, character-hardening and positive real-life experiences, thoughts about the transience of life, the desire to give hope and kindness to the patient. Nurses’ personal experiences of crises and losses lead to empathy and compassion for their patients. Nurses reveal the nobility of patients by looking at each patient as a full-fledged person with the hope of recovery; and own nobility through professionalism, creating an empathetic relation with patients.